EFEKTIVITAS PENYELESAIAN PERSELISIHAN PERBURUHAN HUBUNGAN INDUSTRIAL OLEH DINAS TENAGA KERJA DI KOTA PEKANBARU MELALUI MEDIASI - Bachtiar, Maryati; Hasanah, Ulfia; ', Rosmaneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The legislation in the labor-settlement process first applied in Indonesia is through Emergency Law No. 16 of 1951 on Labor Completion through Mediation. The law provides a decision in the form of a recommendation to the parties to the dispute. The manner in which labor disputes are settled in accordance with Law Number 22 Year 1957 concerning Settlement of Labor Disputes that hold on to the principle of consensus for consensus stand at the first stage, in the event of a dispute, the settlement shall be submitted to the disputing parties. The industrial relations cases that enter the Manpower Office in Pekanbaru City include demands for wage improvement, welfare, jamsostek membership, workers / labor union as well as termination of employment, industrial relations disputes ranging from normative demands such as minimum wage, leave status, work and overtime pay.The entire dispute above is an industrial relations dispute as defined in the provisions of Article 1 number I of Act No. 2 of 2004 concerning Industrial Relations Dispute Settlement provides a definition of Industrial Relations Disputes are disagreements that result in a conflict between employers or the combination of employers with workers / laborers or unions workers / labor unions due to disputes over rights, interest disputes, disputes over disputes, and disputes between trade unions / labor unions within a company.From the results of research problems there are two main things that can be concluded. First, the process of mediation in the Office of Manpower of Pekanbaru City, has not been effective because the number of cases coming into the Office of Manpower Pekanbaru as much as 779 from 2012-2016 can only be completed 331 cases from 2012-2016. This proves that the mediation carried out by the mediator in Pekanbaru City Manpower Office has not been effective in resolving industrial relations disputes in Pekanbaru City. Second, the obstacles experienced so inefficient and effective in the mediation session at Pekanbaru City Manpower Office is the difficulty of uniting the interests of both parties, the lack of mediators and the ability of each different mediator, as well as adequate courtroom facilities. Suggested authors: First, it is expected that the parties to the dispute, prefer the form of settlement of industrial relations disputes through non-litigation channels through mediation. Secondly, in the mediation session proceeded smoothly by the Municipal Labor Office of Pekanbaru City should provide a special room for mediation to ensure its effectiveness is maintained so that both parties can exchange thoughts to unify their two interests. So the mediator also easily decide the results of the trial that goes well.Keywords: Dispute - Relationship - Industrial - Labor